Age and follow-up time affect the prognostic value of the ECG and conventional cardiovascular risk factors for stroke in adult men. Issue 8 (13th July 2007) - Ström Möller, Christina; Häggström, Jonas; Zethelius, Björn; Wiberg, Bernice; Sundström, Johan; Lind, Lars
Abstract : Objectives: To explore whether the predictive power of mid-life ECG abnormalities and conventional cardiovascular risk factors for future stroke change over a 30-year follow-up period, and whether a repeated examination improves their predictive power. Design and setting: Longitudinal population-based study. Participants: 2322 men aged 50 years, with a follow-up period of 30 years. 1221 subjects were re-examined at age 70 years Main outcome measure: Risk for fatal and non-fatal stroke during three decades of follow-up. Investigations included resting ECG and traditional cardiovascular risk factors. Results: When measured at age 50 years, ST segment depression and T wave abnormalities, together with ECG-left ventricular hypertrophy, were of importance only during the first 20 years, but regained importance when re-measured at age 70 years. Blood pressure was a significant predictor for stroke over all three decades of follow-up. In elderly people only, there is evidence that apolipoprotein A1 may protect from future stroke. Conclusion: Mid-life values for blood pressure and ECG abnormalities retain their predictive value over long follow-up periods even though they improved in predictive power when re-measured in elderly people. Despite lower prevalence, ECG abnormalities had greater impact at age 50 years than at age 70 years. By contrast, apolipoprotein A1 was protective for future stroke only at age 70 years.